WordPress 5 theme development academy with Bootstrap v4 (Packt Publishing, 2019)
"This course will equip you with the skills you need to build a fully custom responsive WordPress theme, completely from scratch. You'll no longer need to search for other themes and try to modify them to suit your project as this course will help you build almost any type of WordPress website. You'll begin by building a static version of the 'Tranquil Spa' project using the popular Bootstrap 4 framework. You'll also get up to speed with Bootstrap, exploring responsive design, layout, and the grid system, classes, and utilities creating forms, navbars, adding icons using Font Awesome 5 and much more. Once you have the project looking exactly how you want it, you'll then move on to converting it to WordPress. You will not only perform a basic theme conversion but also cover some of the more challenging concepts and try to make your theme fully customizable by the end-user too. By the end of this course, you'll have gained the skills you need to build a WordPress website for your business, family, clients or even for your personal use."--Resource description page